Mental health evaluation during internet blackouts: A case study of Bangladesh Quota Movement - Rafi Mohammad Ariful Islam; Islam Tahidul (ITM Web of Conferences)
This study investigates the psychological effects of internet blackouts during the Bangladesh Quota Movement in July 2024, when the government shutdown internet access to control information flow. The disruption severely affected communication, financial transactions, and access to essential services, exacerbating stress, tension, and feelings of isolation. A survey of 980 participants using 20 questions assessed behavioural, emotional, and psychological impacts, particularly in academic, work, and social contexts. Results revealed varying stress levels, from minimal to extreme, reflecting widespread distress. Machine learning models were employed to classify the stress levels, with the Decision Tree model achieving 55% accuracy, the Random Forest model improving to 67%, and XGBoost performing better than both with over 94% accuracy. These findings highlight the utility of advanced algorithms in modelling mental health impacts, aiding policymakers in preparing targeted interventions and allocating resources to mitigate psychological effects during future disruptions.